Pengaruh Pengungkapan Emisi Gas Rumah Kaca terhadap Nilai Perusahaan dengan Biaya Lingkungan sebagai Variabel Moderasi - Ulum, Miftahul; Agriyanto, Ratno; Warno, Warno (At-Taqaddum, 2020)
Global warming is caused by an increase in greenhouse gas emissions in the atmosphere, so companies must take responsibility for this through activities to reduce emissions. The purpose of this study is to examine whether environmental costs can moderate the disclosure of greenhouse gas emissions against firm value. This research is a type of quantitative analysis. The sampling technique used purposive sampling. The collecting data through literature study, documentation and secondary data from the Indonesia Stock Exchange 2014-2018. The data analysis technique used the WarpPls 4.0 analysis. They are testing the data using the inner model and outer model methods. This study indicates that GHG emission disclosure has a negative and significant effect on firm value. Environmental costs also have a negative and significant impact on firm value. Meanwhile, ecological prices are not able to moderate the impact of GHG emission disclosures on company value.